A festa do milagre de São Roque no município de Amélia Rodrigues – Ba: relações étnico-raciais e a cultura popular em questão - Bruno, Reginalva dos Santos (2019)
The present work focuses on the relationship between Popular Culture and Education and its main objective is to understand the Festival in the Miracle of São Roque in the Municipality of Amélia Rodrigues - Bahia, as a space for educational practices that are established between Ethnic - Racial and Popular Culture. In order to achieve this goal, we use the festival as its object, because it is a celebration that represents the combination of ethnic-racial cultural practices and Afro-Brazilian religiosity that take place in the same place. In this sense, the study had as methodological basis the qualitative approach and as a research strategy we used the contribution of ethnography. As a data collection procedure, we used the conversation tool with community residents and participants of the party and the use of photographs and videos to complete the work with orality, and thus understand the referentials of educational practices that are behind this party in the context of memory, history and local cultural practices, and with this we promote the appreciation of the wealth of knowledge generated in the universe of popular culture. Theoretically, we base this study on the presuppositions of Popular and Decolonial Education, since it deals with education in relation to popular culture, oral tradition and ancestry as a way of resisting the pressure of the processes of domination of modernity / coloniality and schooling mentality thus indicating a way of educating on the way to resistance to colonialism by means of transmissions of knowledge and knowledge between generations while resisting the historical movements of domination. As results, we can point out that popular festivals such as the one that was studied from the cultural, ethnic and social elaboration of a community is a necessary study and has much to contribute with the dialogue about popular culture and educational practices in ethnic-racial contexts , religious and non-formal, because as it was understood with the research is that the Festival of the Miracle of San Roque, educates, therefore is a space for educational practices through the knowledge of nature, religiosity, tradition and ancestrality being therefore a privileged space, full of emotions, life, faith and wisdom